Moniezia benedeni Infection Restrain IgA+, IgG+, and IgM+ Cells Residence in Sheep (Ovis aries) Small Intestine - Han, Luo-Xia; Yao, Wan-Ling; Pan, Jing; Wang, Bao-Shan; He, Wan-Hong; Fan, Xi-Ping; Wang, Wen-Hui; Zhang, Wang-Dong (Frontiers in Veterinary Science, 2022)
Secreted immunoglobulin A (SIgA), IgG and IgM play a crucial role in forming the intestinal mucosal immune barrier, and parasites could disturb the host’s immune response by releasing various immunomodulatory molecules. Moniezia benedeni is an important pathogen parasitizing in the sheep small intestine. It is aimed to explore the residence characteristics of IgA+, IgG+ and IgM+ cells in the sheep small intestine, and the influence of Moniezia benedeni infection on them. Control group (n=6) and infected group (n=6) were selected, respectively, and the three subtype cells residing in the small intestine were systematically observed and analyzed. The results showed that in the Control group, the three types of positive cells were all distributed diffusely, and the total densities in jejunum, duodenum and ileum was gradually declined in turn. Notably, the change trend of IgA+ and IgG+ cells densities were both congruent with the total densities, and the differences among them were significant, respectively (P<0.05); the IgM+ cells density was the highest in duodenum, followed by jejunum and ileum, there was no significant difference between duodenum and jejunum (P>0.05), but both significantly higher than in ileum (P<0.05). In the Infected group, their total densities in duodenum, jejunum and ileum were gradually declined in turn. Notably, the IgA+ and IgM+ cells densities change trend was the same as the total densities, and the differences among them were significant, respectively (P<0.05). The IgG+ cells density in duodenum was the highest, followed by ileum and jejunum and there was significantly difference among them (P<0.05). The comparison results between Control and Infected groups showed that from the duodenum, jejunum to ileum, IgA+, IgG+, and IgM+ cells were all reduced significantly respectively. The results suggest that the three types of positive cells were resided heterogeneously in the small intestinal mucosa, that is showing significant region-specificity; Moniezia benedeni infection could not change their diffuse distribution, but strikingly, reduce their resident densities, and the forming mucosal immune barrier were significantly inhibited. It provided powerful evidence for studying on the molecular mechanism of Moniezia benedeni evasion from immune surveillance by strongly inhibiting the host’s mucosal immune barrier.